Dinamika Psikologis Remaja Pelaku Kekerasan Seksual Studi Kasus di Lembaga Pembinaan Khusus Anak Klas I Kota Kupang - Nursaputri, Prescilia Thahira; Aipipidely, Diana; Wijaya, R. Pasifikus Ch. (International Journal Labs, 2025)
Psychological dynamics refer to the interactions and changes that occur in a person's thoughts, feelings, and behavior when they face and resolve conflicts involving perceptions, attitudes, and behavior. Understanding a person's psychological dynamics can help in understanding their needs and the appropriate ways to help them overcome various psychological problems. This study aims to understand the psychological dynamics of adolescent perpetrators of sexual violence who are undergoing rehabilitation at the Class I Special Child Rehabilitation Institution (LPKA) in Kupang City. This study uses a qualitative method with a case study approach. The research subjects consisted of two children involved in sexual violence cases. Data were collected through in-depth interviews and documentation, supported by interviews with LPKA officers and psychological assessment reports. Data analysis was conducted using thematic analysis techniques based on cognitive, emotional, and interpersonal aspects. The results of the study show that the psychological dynamics of adolescent perpetrators of sexual violence are influenced by parenting patterns, family, past experiences, emotional pressure, and the influence of the social environment. The cognitive aspect of adolescents is characterized by a lack of self-control and understanding of risk, the emotional aspect shows anger, guilt, and regret, while the interpersonal aspect is influenced by negative social circles and poor social skills. This study emphasizes the importance of a guidance approach that not only emphasizes legal aspects but also psychological rehabilitation, the role of family, and the social environment to prevent the recurrence of sexual violence.